Utjecaj grčke tragedije na Drum Song: An Indian Trilogy Gwen Pharis Ringwood - Katarina Žeravica ([sic])
Gwen Pharis Ringwood (1910–1984) is one of the most eminent Canadian playwrights of the 20th century. In her drama Drum Song: An Indian Trilogy which consists of three parts: Maya (Lament for Harmonica, 1959), The Stranger (1971) and The Furies (1981) the author implements her knowledge of First Nations’ traditions and customs. Moreover, it is “in the lives of the Indian tribes [that] Gwen Ringwood had found an elemental struggle for survival that has produced conflicts comparable with those of Greek tragedy” (Perkyns 330). Such conflicts and elements characteristic of Greek tragedy find their place in this trilogy as well. Therefore, the aim of the paper is to analyse those elements, examine their function, the way and form in which they are presented in the trilogy. Keywords: Canada, drama, First Nations, Gwen Ringwood, tradition, tragedy, trilogy